Manual therapy treatment of lumbar radiculopathy: A single case report - J.A. Riley (AOSIS, 2011)
Patients  with  lumbar  radiculopathy  are  often  managed with  manual therapy.  The  aim  of  this  single  case  study  was  to  describe  the outcome of manual therapy treatment of a patient with lumbar radiculopathy.  A 47-year-old female presented with acute, severe left buttock and postero-lateral thigh pain.  Symptom provocation occurred during lumbar flexion, coughing, sneezing, driving and prolonged sitting. her left straight leg raise neurodynamic test was limited and reproduced her pain, as did trigger points in the left lumbar and gluteal muscles. clinical neuro-conduction testing revealed weakness of the big and other toe extensors, as well as eversion and plantar flexion of the left ankle, and a diminished left ankle reflex. This indicated possible involvement of both the l5 and S1 nerve roots.   A  manual  therapy  treatment  approach including  lumbar rotation mobilisations (Maitland approach), massage, trigger point pressure release  and  Transversus  Abdominus muscle activation  was  used.   The  patient  was  symptom  free,  had  full pain-free  range  of  all  lumbar  movements,  a full  pain-free  left  straight leg  raise  neurodynamic  test  and  normal  neurological  conduction  six weeks  after  onset, following seven manual therapy treatments.  Although the results of this case report cannot be generalised, it describes the successful outcome of a patient with severe radicular pain and neurological deficits, whose signs and symptoms  had completely resolved following manual therapy treatment.